2023
DOI: 10.1186/s13098-023-00978-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia in pregnancy and offspring blood pressure: a systematic review and meta-analysis

Abstract: Background Hyperglycemia in pregnancy (HIP) is suggested to be a risk factor for elevated blood pressure (BP) in offspring. However, the empirical evidence was mixed. Thus, this systematic review and meta-analysis was conducted to synthesize current evidence assessing the association between HIP and BP in offspring. Methods We searched PubMed, MEDLINE, and Embase to identify articles published from inception until 9 February 2021. A random-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…SGLT2 inhibitors have shown blood pressure-lowering effects [19]. We did not find significant changes of blood pressure, which was measured as office blood pressure and not the primary focus of the study.…”
Section: Discussionmentioning
confidence: 60%
“…SGLT2 inhibitors have shown blood pressure-lowering effects [19]. We did not find significant changes of blood pressure, which was measured as office blood pressure and not the primary focus of the study.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, a new meta-analysis reported that SGLT2 inhibitors should be explored as an adjuvant medication for first-line antihypertensive treatment in individuals with T2D and hypertension who have a low risk of genital infection. 23…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a new metaanalysis reported that SGLT2 inhibitors should be explored as an adjuvant medication for first-line antihypertensive treatment in individuals with T2D and hypertension who have a low risk of genital infection. 23 The glucose reabsorption into the PCTs is regulated in response to blood glucose level changes and is proportional to the quantity of the filtrate glucose content. The kidney has a tubular maximum renal glucose reabsorption threshold (TmaxG) for reabsorbing glucose, which occurs when the filtered glucose reaches about 19.4 mmol/L/min/1.73 m 2 , which is comparable to a glycemia level of 10 to 11.1 mmol/L.…”
Section: Mechanism Of Action Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…High blood pressure (HBP) and gestational diabetes (GD) are two complications frequently encountered during pregnancy with potentially adverse effects on both the mother and the fetus [ 1 ]. Studies investigating the association between these medical conditions and pregnancy have shown adverse effects on children born to mothers with HBP (higher rates of early-onset cardiovascular disease) and gestational diabetes (increased newborn adiposity with elevated maternal blood glucose) [ 2 ]. In addition, pregnancy-related complications such as hypertensive disorders, GD, preterm birth, and pregnancy loss have been associated with an increased risk of future cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%